Analysis of micro and small business behavior in the adoption of financial applications for the development of an android-based financial application model - Latifah, Nunuk; Wardani, Shanti Ike; Wahyuningsih, Sulistya Dewi (International Journal on Social Science, Economics and Art, 2024)
As a sector that can increase production capacity, MSEs have a significant impact on economic and social progress. However, MSEs still face various obstacles, one of which is manual and traditional financial management. Lack of understanding and knowledge in financial management is the main cause. Using the Theory of Planned Behavior (TPB) approach, this study highlights the development of self-efficacy beliefs and perceived behavioral control, strengthening the relationship between beliefs, attitudes, intentions, and behaviors of MSE actors. The purpose of this study is to examine the financial management behavior of MSEs in Blitar. The method applied is descriptive quantitative. The population in focus is MSEs in Blitar, with a total of 2569, while the sample taken is 135 business actors. The data analysis method used includes descriptive analysis and inferential statistics, with the application of the Structural Equation Model (SEM) approach based on Partial Least Square (PLS). The results of this study indicate that Financial Attitude, Financial Literacy and Financial Knowledge do not affect the Behavioral Intention of business actors. The behavioral intention of business actors is still relatively low in determining financial management attitudes because understanding and skills in management are also still low. This is because they focus more on marketing and sales.